Post-drought growth recovery of tea (Camellia sinensis) under different techniques and doses of biofertilizer applications - Wiharti, Nabila Ragil; Anjarsari, Intan Ratna Dewi; Maxiselly, Yudithia (Universitas Padjadjaran, 2025)
Drought stress is a major limiting factor affecting the growth, yield, and quality of tea (Camellia sinensis). The present study aimed to analyze the success of post-drought growth recovery of tea in response to different techniques and doses of biofertilizer applications. Field experiments were conducted from January to August 2024 in the experimental garden of the Research Institute for Tea and Cinchona, Gambung Blok A8, Bandung. This work was arranged in a split-plot design, consisting of a main plot with two biofertilizer application techniques (foliar feeding and soil drenching) and subplots with four levels of biofertilizer dosage (control (B1), 15 L ha-¹ (B2), 22.5 L ha-¹ (B3), and 30 L ha-¹ (B4), with three replications. The results showed a significant interaction of biofertilizer dose and technique on shoot dry weight and plant growth rate of tea. There was an independent effect of biofertilizer dose on leaf area ratio. Applying a biofertilizer dose of 15 L ha-1 through soil drenching produced the best plant growth rate and shoot dry weight at the 6th harvest.